The Impact of Organizational Support on Employee Work Commitment in Higher Education - Amdayanti, Depi; Kadri, Hanif Al; Widiawati Widiawati (Universitas Jambi, Indonesia, 2023)
This research aimed to determine the effect of organizational support on employee work commitment. The research method used was a quantitative method with correlational descriptive techniques. The research population consisted of 89 civil servants at the Institut Seni Indonesia Padang Panjang. The research sample consisted of 81 people who were determined using the stratified proportional random sampling technique and the Slovin formula. The data collection technique used in this research was a Likert scale questionnaire with five alternative answers. In addition, the data analysis technique used was product-moment correlation and simple linear regression analysis, which was analyzed using the SPSS program. The results showed that organizational support had a positive and significant effect on employee work commitment by 24.6%. The rest is affected by other variables. This research implied that institutions need to increase organizational support so employees can work with high commitment.